2000
DOI: 10.1038/sj.ejcn.1600900
|View full text |Cite
|
Sign up to set email alerts
|

A single dose of tea with or without milk increases plasma antioxidant activity in humans

Abstract: Objective: To investigate the effect of black and green tea consumption, with and without milk, on the plasma antioxidant activity in humans. Design: In a complete cross-over design, 21 healthy volunteers (10 male, 11 female) received a single dose of black tea, green tea (2 g tea solids in 300 ml water) or water with or without milk. Blood samples were obtained at baseline and at several time points up to 2 h post-tea drinking. Plasma was analysed for total catechins and antioxidant activity, using the ferric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
158
1
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(175 citation statements)
references
References 21 publications
9
158
1
7
Order By: Relevance
“…It allows the substantial measuring of the blood concentration of antioxidants as agents able to reduce the iron from its ferric (Fe3+) to its ferrous (Fe2+) form. The test provides a global measurement of many antioxidants including uric acid, ascorbic acid, α-tocopherol, glutathione, carotenoids and so on [32]. The results obtained in our study indicate a signifi cant decrease in FRAP concentration (p<0.05) after exercise in June, before antioxidant supplementation was implemented (Table 1).…”
Section: Discussionsupporting
confidence: 60%
“…It allows the substantial measuring of the blood concentration of antioxidants as agents able to reduce the iron from its ferric (Fe3+) to its ferrous (Fe2+) form. The test provides a global measurement of many antioxidants including uric acid, ascorbic acid, α-tocopherol, glutathione, carotenoids and so on [32]. The results obtained in our study indicate a signifi cant decrease in FRAP concentration (p<0.05) after exercise in June, before antioxidant supplementation was implemented (Table 1).…”
Section: Discussionsupporting
confidence: 60%
“…Some studies indicate a decrease in antioxidant potential of tea after adding milk [31], others signal an increase in the antioxidant value [32]. There are also studies known where no change in the antioxidant properties of tea was observed after adding milk [33].…”
Section: Influence Of Additives On the Antioxidant Properties Of Teamentioning
confidence: 99%
“…This may decrease the bioavailability and antioxidant potential of polyphenols in vivo (14)(15)(16)(17)(18), thus negating the antiathersclerotic benefit of black tea. In contrast, others report no masking effects of milk addition on increases in plasma antioxidant potential (19) and concentrations of catechins (20) or flavonols (21) after the consumption of black tea. However, interpretation of such studies is difficult as they consider different polyphenolic tea components and use antioxidant assay systems differing in choice of oxidation source, target, and type of measurement used (2,22,23).…”
Section: Introductionmentioning
confidence: 98%